A 4-year-old boy with progressive penile enlargement and accelerated growth - Rahman, Md Ashiqur; Ahmed, Nasir; Haq, Tahniyah; Selim, Shahjada; Fariduddin, Md (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
A 4-year-old boy presented with progressive penile enlargement, pubic hair, acne, and aggressive behaviour for two years. Physical examination revealed that height was greater than the 95th percentile. Tanner stages showed advanced pubertal signs. His bone age was also advanced compared to chronological age. Laboratory findings were suggestive of peripheral precocious puberty. Abdominal imaging showed a mass at the right adrenal gland. The patient underwent a right open adrenalectomy. There was a well-circumscribed mass with no invasion of surroundings. The histopathology study was consistent with an adrenocortical tumor which was confirmed to be an adenoma by Immunohistochemistry. Postoperatively his cortisol and testosterone levels were normal. Follow-up at 6 months showed that there was secondary activation of the hypothalamic-pituitary-gonadal axis, a complication of prolonged exposure to androgens. J Assoc Clin Endocrinol Diabetol Bangladesh, January 2024; 3 (1): 34-37